2022
DOI: 10.3390/jfb13030090
|View full text |Cite
|
Sign up to set email alerts
|

A Bibliometric Analysis of Electrospun Nanofibers for Dentistry

Abstract: Electrospun nanofibers have been widely used in dentistry due to their excellent properties, such as high surface area and high porosity, this bibliometric study aimed to review the application fields, research status, and development trends of electrospun nanofibers in different fields of dentistry in recent years. All of the data were obtained from the Web of Science from 2004 to 2021. Origin, Microsoft Excel, VOSviewer, and Carrot2 were used to process, analyze, and evaluate the publication year, countries/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 137 publications
0
3
0
Order By: Relevance
“…Presently, their application is largely restricted to periodontal regeneration, whereby polycaprolactone (PCL) is usually employed for this purpose. However, owing to the global upsurge in research on electrospun dental materials, bone regeneration, tissue regeneration, and cell differentiation and proliferation, it is expected that the scope of their clinical use will expand considerably [ 35 ] Nonetheless, there is a paucity of studies as a part of which the impact of the incorporation of PA nanofibers into dental composite materials on their mechanical properties is evaluated. In extant research, the focus is primarily given to the strategies for improving the quality of polymethyl methyl acrylate used in the production of dental prostheses by using electrospun fibers as reinforcement.…”
Section: Resultsmentioning
confidence: 99%
“…Presently, their application is largely restricted to periodontal regeneration, whereby polycaprolactone (PCL) is usually employed for this purpose. However, owing to the global upsurge in research on electrospun dental materials, bone regeneration, tissue regeneration, and cell differentiation and proliferation, it is expected that the scope of their clinical use will expand considerably [ 35 ] Nonetheless, there is a paucity of studies as a part of which the impact of the incorporation of PA nanofibers into dental composite materials on their mechanical properties is evaluated. In extant research, the focus is primarily given to the strategies for improving the quality of polymethyl methyl acrylate used in the production of dental prostheses by using electrospun fibers as reinforcement.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the hydrophobicity and low degradation of PCL can act as a barrier preventing the diffusion of toxic byproducts from the restorative filling material [21]. Several studies have demonstrated the potential of this synthetic polymer for craniofacial bioengineering strategies, which is widely used in dental material applications [18,[22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, these analyses have only described trends. 19,20 Indeed, some analyses have indicated that there were trends 21 ; that there was no clear trend 22 ; that the increase in the number of publications was linear, 23 polynomial, 24 or exponential 25 ; or that its trends followed a discontinuous regression pattern. 26 This information will guide researchers in dentistry when they make decisions about which journal to publish in and therefore to which publisher they should submit their article.…”
Section: Introductionmentioning
confidence: 99%